Comparison of Atrial Fibrillation in the Young versus That in the Elderly: A Review - Rajiv Sankaranarayanan; Graeme Kirkwood; Katharine Dibb; Clifford J. Garratt (Cardiology Research and Practice)
The incidence and prevalence of atrial fibrillation (AF) are projected to increase significantly worldwide, imposing a significant burden on healthcare resources. The disease itself is extremely heterogeneous in its epidemiology, pathophysiology, and treatment options based on individual patient characteristics. Whilst ageing is well recognised to be an independent risk factor for the development of AF, this condition also affects the young in whom the condition is frequently symptomatic and troublesome. Traditional thinking suggests that the causal factors and pathogenesis of the condition in the young with structurally normal atria but electrophysiological “triggers” in the form of pulmonary vein ectopics leading to lone AF are in stark contrast to that in the elderly who have AF primarily due to an abnormal substrate consisting of fibrosed and dilated atria acting in concert with the pulmonary vein triggers. However, there can be exceptions to this rule as there is increasing evidence of structural and electrophysiological abnormalities in the atrial substrate in young patients with “lone AF,” as well as elderly patients who present with idiopathic AF. These reports seem to be blurring the distinction in the pathophysiology of so-called idiopathic lone AF in the young versus that in the elderly. Moreover with availability of improved and modern investigational and diagnostic techniques, novel causes of AF are being reported thereby seemingly consigning the diagnosis of “lone AF” to a rather mythical existence. We shall also elucidate in this paper the differences seen in the epidemiology, causes, pathogenesis, and clinical features of AF in the young versus that seen in the elderly, thereby requiring clearly defined management strategies to tackle this arrhythmia and its associated consequences.